Benefit of carotid revascularisation for women with symptomatic carotid stenosis: protocol for a systematic review. Issue 11 (11th November 2019) - Bereznyakova, Olena; Dewar, Brian; Dowlatshahi, Dar; Howard, Virginia; Hamel, Candyce; Gocan, Sophia; Fedyk, Mark; Shamy, Michel
Abstract : Introduction: Carotid intervention in the form of endarterectomy or stenting is the current standard of care for the majority of patients with symptomatic high-grade carotid stenosis. However, some randomised controlled trials (RCT) have demonstrated that women benefited significantly less from intervention than men. It is unclear if this is a true phenomenon or a study sampling artefact, as women were severely under-represented in all RCTs of carotid revascularisation. A systematic review is needed to summarise the existing data and to answer the question of whether a women-only trial for symptomatic patients with ipsilateral carotid stenosis is scientifically necessary and ethically permissible. Methods and analysis: We will systematically search Medline, Embase, PubMed and the Cochrane libraries for all studies with data from RCTs that included women and compared either endarterectomy with stenting or revascularisation (by means of endarterectomy or stenting) with medical therapy in patients with symptomatic carotid stenosis. Search dates will be restricted to 1991–2018. Two reviewers will conduct screening search results, study selection, data extraction and quality assessment. We will include all studies reporting outcomes of interest. Planned subgroup analysis based on revascularisation technique, degree of stenosis and timing of intervention from the index event will be conducted with enough data. Ethics and dissemination: This research is exempt of ethics approval as no primary data will be collected. The results will be published in peer-reviewed journals and disseminated through national and international-level conferences and scientific meetings. The result of this comprehensive review will provide useful information on whether further RCTs are required to study a women-only population with symptomatic carotid disease. PROSPERO registration number: CRD42019134967.